Rapid formation of granules coupling n-DAMO and anammox microorganisms to remove nitrogen. (15th April 2021) - Liu, Chunshuang; Liu, Tao; Zheng, Xiaoying; Meng, Jia; Chen, Hui; Yuan, Zhiguo; Hu, Shihu; Guo, Jianhua
Highlights: Granules coupling anammox and n-DAMO are obtained in 6 months. Using anammox granules as biotic carriers and stepwise increasing upflow velocity are two keys. Cryosection FISH and sequencing are used to reveal microbial stratification in granules. Anammox bacteria dominate outer layer, while n-DAMO archaea occupy inner layer. A high rate of 1.0 kg N/m 3 /d is achieved from synthetic sidestream wastewater. Abstract: Granular sludge exhibits unique features, including rapid settling velocity, high loading rate and relative insensitivity against inhibitors, thus being a favorable platform for the cultivation of slow-growing and vulnerable microorganisms, such as anaerobic ammonium oxidation (anammox) bacteria and nitrite/nitrate-dependent anaerobic methane oxidation (n-DAMO) microorganisms. While anammox granules have been widely applied, little is known about how to speed up the granulation process of n-DAMO microorganisms, which grow even slower than anammox bacteria. In this study, we used mature anammox granules as biotic carriers to embed n-DAMO microorganisms, which obtained combined anammox + n -DAMO granules within 6 months. The results of whole-granule 16S rRNA gene amplicon sequencing showed the coexistence of anammox bacteria, n-DAMO bacteria and n-DAMO archaea. The microbial stratification along granule radius was further elucidated by cryosection-16S rRNA gene amplicon sequencing, showing the dominance of n-DAMO archaea and anammox bacteria at inner and outer layers, respectively. Moreover, the images of cryosection-fluorescence in situ hybridization (FISH) verified this stratification and also indicated a shift in microbial stratification. Specifically, n-DAMO bacteria and n-DAMO archaea attached to the anammox granule surface initially, which moved to the inner layer after 4-months operation. On the basis of combined anammox + n -DAMO granules, a practically useful nitrogen removal rate (1.0 kg N/m 3 /d) was obtained from sidestream wastewater, which provides new avenue to remove nitrogen from wastewater using methane as carbon source. Graphic abstract: Image, graphical abstract